Managerial Models and Their Contribution to the Successful Use of Financial Applications - L Puspitawati (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study examines the suitability of the managerial model (the strategy, support and competence of managers) on the successful use of financial applications for insurance companies registered with the Indonesian Financial Services Authority (OJK). Quantitative methods used to confirm the proposed model and predict the magnitude of the influence that arises between the variables studied. Primary data was collected by distributing questionnaires to 313 accounting and finance managers of insurance companies registered OJK Indonesia and 160 sample sizes were collected through a simple random technique. Data analysis used Covarian Base Structural Equation Model (CB-SEM) with Lisrell 8.5 software. The results of this study have succeeded in confirming the conceptual model developed by researcher and proving that managerial model variables have an effect on the successful use of financial applications in insurance companies registered OJK Indonesia. This research proves that the successful of using financial application depends on the relevance of the user. The Managerial Model shows that the right management strategy and top management support as well as adequate managerial competence effectively make the system more flexible, integrated, easy to access which in turn creates user satisfaction and intensive use of the system in an organization. The successful use of applications in an organization encourages the company's operational activities to run effectively and efficiently and to achieve competitive advantage